THE EFFECTS OF POLITICAL CONNECTIONS, CORPORATE GOVERNANCE, AND ENTERPRISE RISK MANAGEMENT ON FIRM VALUE IN BANKING SUB-SECTOR COMPANIES - Etanntyo, Dimas Pandu; Suryaningsum, Sri (Count : Journal of Accounting, Business and Management, 2024)
Firm value is a calculation that describes the public's view of the company. The company value in this study will be measured using Tobin's Q. This study aims to provide an empirical explanation regarding the influence of the independent variables of political connection, corporate governance, and enterprise risk management. This study took the population of banking companies listed on the Indonesia Stock Exchange (IDX) for 2019-2023. The sample in this study was selected using purposive sampling method to find samples that fit the criteria and 226 samples were selected. The multiple linear regression analysis method was chosen for this study. This study has results, the three independent variables of political connection, corporate governance, and enterprise risk management have a partial and simultaneous effect on firm value.